(untitled) (Research, Society and Development, 2020)
The study aimed to evaluate limnological quality in the Curral de Arame stream, to determine concentrations of metals in water and sediments, to assess whether the types of land use and cover interfere in aquatic quality. In addition to correlating land use and cover in relation to the concentrations of metals in the water between the dry and rainy periods and to investigate the potential non-carcinogenic risks of metals in the water for aquatic biota. The pH values, in the dry period, were lower than the limit established by Brazilian legislation in the medium and low portion of the stream. Fe in water exceeded the limit established by the Brazilian resolution, in the four locations. Metal concentrations in sediments were within safe limits for aquatic life. The Curral de Arame stream showed reduced riparian vegetation in some places, due to the expansion of agricultural activities. We found, in the dry and rainy periods, a negative correlation between the proportions of agriculture and forest fragments, showing when there is an increase in agricultural areas, the reverse occurs to the reduction of native vegetation cover. In the rainy season, there was a negative and significant correlation between forest fragments compared to Fe in the water in the Curral de Arame stream, demonstrating when there is greater supply of vegetation, which reduces the carrying of contaminants in the course of the aquatic system. In the Curral de Arame stream, in the dry and rainy periods, it presented a non-carcinogenic risk in the water for the aquatic biota in relation to the Fe values. In this sense, the Curral de Arame stream is experiencing some type of environmental stress, mainly due to the reduction of native vegetation cover around this aquatic environment.